(untitled) (Acta Scientiarum. Health Sciences, 2017)
Oral Lichen Planus (OLP), a chronic inflammatory disease of unknown etiology, which affects the skin and/or mucosal tissues, is an autoimmune disease (pathology) of special interest to dentists due to its oral manifestations and its possible association with Hepatitis C virus (HCV). Although a possible association has been extensively discussed in the literature, the results have been controversial. So that the relationship between Oral Lichen Planus (OLP) and infection by HCV (OLP-HCV) may be investigated, current study conducted an epidemiological survey of all OLP cases diagnosed in two reference projects, with regard to diagnosis, treatment and epidemiology of oral lesions in Maringá, Paraná, Brazil. In addition, the clinical case of a patient with HCV and the clinical manifestation of severe OLP will be provided. A total of 3,488 clinical records of biopsies performed between 1994 and 2014 and 85 cases of OLP were selected for the present study. The reticular type of OLP showed significant prevalence but only 2.3% of OLP cases revealed any association with HCV.